Educar, assistir, moralizar : a experiência dos clubes de mães em Limoeiro do Norte CE (1960 1990) - Rodrigues, Maria da Conceição Silva (2011)
The Clubs of Mothers in Limoeiro the Norte, Ceara, are organizations of social action that emerged in the public Brazilian mid-twentieth century and throughout its history, gain expressiveness in the context of Latin America. They are spaces that gather women-mothers around of multiple interests such as welfare, female identity, domestic education, the spread of Christian morality by its relationship with the Catholic Church, as well as the spread of the ideals hygienists. This research work methodically with oral testimonies of women who experience this training. It is also used to compose the analysis, as various documents, records and certificates of foundation, statutes of Clubs, and projects of courses offered and Tombo books of Parish of Limoeiro do Norte. The central issue of the study is to understand the dynamics of assisting, educating and moralizing, present in these organizations, while seeking to understand how some women who experience this space build their experiences in the midst of dynamics referred. The analysis of these experiences enabled to understand the tensions experienced by them daily, the paradigms of domination, but also how these women forging resistors, and reframe their womanhood